Implementasi Sistem Pendaftaran Berbasis Android dan Web pada Klinik Terapis Gigi dan Mulut Bambang Hariyadi, Amd.Kes - Irawan, Devi; Yanuarti, Elly; Fitriyani; Wahyuningsih, Delpiah; Buulolo, Karuniaman; Wau, Kristine (Jurnal Informatika, 2025)
The rapid advancement of information technology each year has driven digital transformation across various sectors, including healthcare services. One significant innovation is the digitalization of patient registration processes, which were previously conducted manually and often resulted in long queues and inefficiency. This study aims to develop and implement an Android and web-based registration system at the Dental and Oral Therapist Clinic of Bambang Hariyadi, Amd.Kes, in order to enhance efficiency and improve the patient experience. The system development method includes needs analysis through interviews and literature studies, user interface and system architecture design, implementation of both mobile and web applications, and evaluation based on user feedback. The application allows patients to independently register, schedule appointments, and receive periodic treatment reminders through their mobile devices or computers. Evaluation results indicate a significant improvement in registration efficiency, reduced waiting times, and increased patient satisfaction with the clinic’s services. Therefore, the implementation of this system is considered effective in supporting the digitalization of registration services in healthcare facilities, particularly in dental and oral therapy practices.